PENYEDERHANAAN IZIN USAHA BAGI PELAKU USAHA MIKRO DAN KECIL DARI PERSPEKTIF HUKUM: STUDI DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA (SIMPLIFICATION OF BUSINESS LICENSING FOR MICRO AND SMALL INTERPRISES) - Monika Suhayati (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2016)
Legality of micro and small enterprises (UMK) through licensing is very important for UMK to be able to access capital in expanding its business and compete with the products, goods and services from domestic and other countries. Licensing for UMK stipulated in Presidential Decree Number 98 Year 2014 regarding Licensing for Micro and Small Enterprises, is a simplified form of licensing UMK. The subject matter to be analyzed in this paper is the urgency of simplification of business licensing to business development for UMK, the implementation of the licensing of UMK in the Province of Yogyakarta, and the constraints. This problem will be analyzed using the concept of economic democracy (Article 33 of the Indonesian Constitution) and the right to work and to a decent living (Article 27 paragraph (2) of the Indonesian Constitution). In the Province of Yogyakarta, the regulation has implemented only in Bantul District and Yogyakarta City. Some constraints, not all districts has delegate the authority to grant IUMK as mandated by the regulation, lack of awareness of policy makers of the importance of IUMK, the obligation of UMK to pay 1% of turnover taxes after owning the IUMK, and the financing of publishing IUMK in the district is not budgeted yet in the budget of each district or city. As a suggestion from this study, first, Yogyakarta Provincial Government needs to socialize the IUMK to the district and the city which has not issued the regulation of regents or mayors. Secondly, the district governments need to budget financing IUMK publication in the budget of each district. Third, the need to socialize the importance of income tax payments for the development of UMK by the tax officials.ABSTRAKLegalitas usaha mikro dan kecil (UMK) melalui perizinan sangat penting bagi UMK untuk dapat mengakses permodalan dalam mengembangkan usahanya dan bersaing dengan produk barang dan jasa dari dalam dan luar negeri. Perizinan untuk UMK diatur dalam Peraturan Presiden Nomor 98 Tahun 2014 tentang Perizinan untuk Usaha Mikro dan Kecil yang merupakan suatu bentuk penyederhanaan perizinan UMK. Pokok permasalahan yang hendak dianalisis dalam tulisan ini yaitu urgensi dari penyederhanaan perizinan usaha bagi pengembangan usaha pelaku UMK serta pelaksanaan perizinan UMK di Provinsi DIY dan kendalanya. Permasalahan ini akan dianalisis menggunakan konsep Demokrasi Ekonomi (Pasal 33 UUD Tahun 1945) dan konsep Negara Hukum Kesejahteraan. Di Provinsi DIY, Perpres IUMK baru dilaksanakan di Kabupaten Bantul dan Kota Yogyakarta. Kendala dalam pelaksanaannya yaitu belum semua kabupaten mendelegasikan kewenangan pemberian IUMK kepada camat sebagaimana mandat Perpres IUMK, adanya kewajiban pembayaran pajak oleh UMK yang telah memiliki IUMK sebesar 1% dari omset, dan pembiayaan penerbitan IUMK di kecamatan belum teranggarkan di APBD masing-masing kabupaten/kota. Sebagai saran dari kajian ini, pertama, Pemerintah Provinsi DIY perlu melakukan sosialisasi mengenai IUMK kepada pemerintah kabupaten dan kota yang belum mengeluarkan peraturan bupati/walikota. Kedua, pemerintah kabupaten dan kota di Provinsi DIY perlu menganggarkan pembiayaan penerbitan IUMK di kecamatan dalam APBD masing-masing kabupaten dan kota. Ketiga, perlu sosialisasi pentingnya pembayaran PPh untuk pengembangan usaha UMK oleh pihak aparatur pajak.